Neutralizing gender in role nouns: investigating the effect of ə in written and oral Italian - Abbondanza, Martina; Galimberti, Valeria; Bonomi, Valeria; Reverberi, Carlo; Durante, Federica; Foppolo, Francesca (Frontiers in Communication, 2025)
In languages like Italian, all nouns have grammatical gender, which in most cases can be inferred from word endings. Nouns that refer to people may also convey information about the referent’s gender (i.e., semantic gender), as in the case of transparent gender-marked nouns (e.g., maestro[MASC]/maestra[FEM], ‘male/female school teacher’). Gender remains unspecified in the case of bigender nouns (e.g., cantante[MASC, FEM], ‘singer’), though these may carry gender stereotypical associations (dirigente[MASC, FEM], ‘manager’, typically associated with men). To overcome the binary gender distinction in language, one proposal for Italian gender inclusive language introduces the schwa (ə) as a neutral word-ending (e.g., maestrə). There is still no scientific evidence on the efficacy of gender-neutral forms in promoting Italian speakers’ perceptions of these role nouns as gender-neutral and of their potential to reduce grammatical and/or gender stereotypical associations. Here, we present three rating studies to investigate gender associations of role nouns presented in isolation. In Study 1 (N = 106) bigender and gender-marked role nouns with their canonical grammatical endings were tested; in Study 2 (N = 121) we tested bigender nouns and neutralized nouns ending in -ə in the written modality, while in Study 3 (N = 75) in the auditory modality. Results showed that, ə only partially reduces gender associations of neutralized role nouns. When the neutralized form of the noun evokes the masculine (e.g., direttorə, ‘director’) or when a noun carries a strong stereotypical association, as in the case of stereotypically feminine nouns like casalingə (‘homemaker’), the neutralized form seems ineffective. Furthermore, schwa in the written modality appeared more effective than the auditory modality. We discuss our findings also in light of trade-offs of this proposal from linguistic and sociolinguistic perspectives.